Investigation of the Self-Discharge Behavior of Lithium-Sulfur Batteries. Issue 6 (8th March 2016) - Knap, V.; Stroe, D.-I.; Swierczynski, M.; Teodorescu, R.; Schaltz, E.
Abstract : Lithium-Sulfur (Li-S) batteries represent a perspective energy storage technology, which reaches very high theoretical limits in terms of specific capacity, specific energy, and energy density. However, Li-S batteries are governed by the polysulfide shuttle mechanism, which causes fast capacity fade, low coulombic efficiency, and high self-discharge rate. The self-discharge is an important characteristic of Li-S batteries for both practical applications and laboratory testing, which is highly dependent on the operating conditions. Thus, to map and to understand the Li-S self-discharge behavior under various conditions, such as depth-of-discharge, temperature, and idling time, a set of experiments were performed in this work on 3.4 Ah Li-S pouch cells. The results are systematically presented in form of open-circuit voltages during idling and self-discharge separated into reversible and irreversible capacity loss. Furthermore, estimation of the actual high voltage plateau capacity based on a self-discharge constant was performed according to an earlier proposed methodology; however, the method needs further improvements in order to estimate this capacity accurately for all conditions.